1990
DOI: 10.1152/ajpheart.1990.259.6.h1703
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in regulation of regional cerebral blood flow in sensory cortex

Abstract: We have previously demonstrated that rat pial arterioles located on the somatosensory cortex dilated in response to contralateral sciatic nerve stimulation (SNS). We hypothesized that the vasodilation was mediated by adenosine, released as a result of somatosensory cortex activation. To test this hypothesis, we examined the effects of SNS (0.15-0.2 V, 5 ms, 5 Hz for 20 s) on pial arterioles under conditions of altered adenosine availability. Cerebrospinal fluid (CSF) adenosine was altered by perfusing mock CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 0 publications
5
65
2
2
Order By: Relevance
“…This experi mental paradigm allows examination of the cerebral microcirculation during cortical activation. In a pre vious study using this technique, we found that changes in adenosine availability altered the arteri olar response, supporting the hypothesis that ade nosine is involved in the regional metabolic regula tion ofCBF (Ko et al, 1990). On the other hand, the pial vessels are known to be innervated by fibers arising in extracerebral sympathetic and para sympathetic fibers (Busija and Heistad, 1984;Ed-nucleus basalis magnocellularis (the major source of in tracerebral acetylcholine neurons, n = 7).…”
supporting
confidence: 73%
“…This experi mental paradigm allows examination of the cerebral microcirculation during cortical activation. In a pre vious study using this technique, we found that changes in adenosine availability altered the arteri olar response, supporting the hypothesis that ade nosine is involved in the regional metabolic regula tion ofCBF (Ko et al, 1990). On the other hand, the pial vessels are known to be innervated by fibers arising in extracerebral sympathetic and para sympathetic fibers (Busija and Heistad, 1984;Ed-nucleus basalis magnocellularis (the major source of in tracerebral acetylcholine neurons, n = 7).…”
supporting
confidence: 73%
“…During this metabolic response, several compounds, which mediate the vasodilatory haemodynamic response in the surrounding microcirculation, are produced. The principal vectors of this vascular response are K + ions (Paulson and Newmann 1987;Kuchinsky 1997), H + ions (Kuchinsky 1997), nitric oxide (NO; Northington et al 1992;Dirnagl et al 1993) and adenosine (Ko et al 1990;Dirnagl et al 1993), although peptides (Edvinsson 1985), prostaglandins (PG; Leer et al 1993) and kinines (Itakura and Okuno 1993) have also been implicated in these processes. These events occur near the synapses and a number of arguments suggest that regional CBF primarily re¯ects local synaptic activity (Jueptner and Weiller 1995).…”
Section: Cerebral Blood¯ow As a Marker Of Neuronal Activity During Sleepmentioning
confidence: 99%
“…Several studies have been published docu menting increases in adenosine concentration in brain, interstitial fluid, and CSF under conditions in which oxygen supply to the brain is decreased (Winn et al, 1981b;Van Wylen et al, 1986;Phillis et al , 1987). Moreover, adenosine receptor antag onists and uptake inhibitors have been utilized ex tensively in studies attempting to define the role of this nucleoside in blood flow regulation (Ko et al , 1990;Morii et al , 1987;Park and Gidda y, 1990;Phillis et al, 1989).…”
Section: Controlmentioning
confidence: 99%